2006
DOI: 10.1007/s11090-006-9006-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laminar and Turbulent Thermal Plasma Jet Characteristics—A Modeling Study

Abstract: Modeling results are presented to compare the characteristics of laminar and turbulent argon thermal plasma jets issuing into ambient air. The combined-diffusion-coefficient method and the turbulence-enhanced combined-diffusion-coefficient method are employed to treat the diffusion of ambient air into the laminar and turbulent argon plasma jects, respectively. It is shown that since only the molecular diffusion mechanism is involved in the laminar plasma jet, the mass flow rate of ambient air entrained into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 28 publications
(81 reference statements)
8
51
1
Order By: Relevance
“…4-7 are roughly consistent with the modeling predictions of Ref. [19][20][21], although the entrained gases are somewhat different (nitrogen is used in this experiment while air is used in the modeling studies). As mentioned above, the plasma-forming gas (argon) of the plasma torch is supplied through three channels, i.e.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…4-7 are roughly consistent with the modeling predictions of Ref. [19][20][21], although the entrained gases are somewhat different (nitrogen is used in this experiment while air is used in the modeling studies). As mentioned above, the plasma-forming gas (argon) of the plasma torch is supplied through three channels, i.e.…”
Section: Resultssupporting
confidence: 78%
“…It was shown that the entrained air mass flow-rate almost linearly increases with increasing jet-inlet gas velocity (or mass flow rate) for a fixed jet-inlet temperature and with increasing axial distance. And the values of the entrained gas mass flow rate normalized to the jet-inlet mass flow rate (m 1 /m 0 ) were as large as about 16 at the axial distance of 100 mm [19]. The present experimental results presented in Figs.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The main assumptions used in the modeling study of the plasma jet include steady, laminar and axi-symmetrical flow with negligible swirling velocity component; local thermodynamic equilibrium (LTE) and optically thin plasma; diffusion of the ambient air into the plasma jet can be handled by the combined-diffusion-coefficient method [9][10][11][12][13]. The governing equations including the mass, momentum, energy, and gas species conservation equations in the cylindrical coordinate system are similar to those used in [11][12][13] and can be written as follows:…”
Section: Laminar Plasma Impinging-jetmentioning
confidence: 99%